Perception and purchase behavior of young Indian consumers towards Chinese products under the backdrop of their economic and political rivalry. Issue 1 (3rd September 2020) - Sengupta, Angan
Abstract : Objective: This study examines the impact of perceptions of young Indian adults about Chinese products in Indian markets upon their purchase behavior, especially after the border conflict in Doklam. Methodology: We have analyzed data collected from a randomly selected sample of 339 educated urban individuals (18–40 years). Binary logistic regression was conducted to estimate the likelihood of buying Chinese products given their level of acceptance among those respondents who are aware of the Indo‐China conflict. Findings: Young Indians mainly focus on quality and price while purchasing a product, and not the country‐of‐origin (COO). Those who took the social media messages to ban Chinese products seriously, concerned about the dominance of Chinese products in the Indian market, and check if the COO is China demonstrate significantly aversive purchase intention towards Chinese products. On the contrary, the odds of purchase decision making getting influenced by Indo‐China conflict is significantly lower for them who have some preference for Chinese products over its Indian substitutes. Conclusions: Feeling of animosity does not result in considerable hostility against the willingness to buy Chinese products, when price, quality, brand awareness, and non‐availability of appropriate Indian substitutes matter more. However, if the sense of animosity is utilized well, Indian manufacturers, especially the MSME sectors, can gain entrepreneurial opportunities and mileage.